2014
DOI: 10.3945/ajcn.114.090316
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding and anti-tissue transglutaminase antibody concentrations in the Generation R Study

Abstract: Delayed introduction of gluten beyond the age of 6 mo does not increase the risk of CDA. In addition, breastfeeding for ≥6 mo does not decrease the risk of CDA in children at 6 y of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 32 publications
1
44
0
3
Order By: Relevance
“…However, it was unclear whether it provided long-term prevention against CD or only delayed the onset of the disease [24,[35][36][37] . Results of the recently published cohort studies did not confirm the protective effect of breastfeeding at the time of gluten introduction on developing CD [31,38] . Also, the pooled results for 7 observational studies showed that breastfeeding at the time of gluten introduction has no effect on the risk of developing CD compared with formula feeding (OR 0.88, 95% CI 0.52-1.51) [10] .…”
Section: Breastfeeding At the Time Of Gluten Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…However, it was unclear whether it provided long-term prevention against CD or only delayed the onset of the disease [24,[35][36][37] . Results of the recently published cohort studies did not confirm the protective effect of breastfeeding at the time of gluten introduction on developing CD [31,38] . Also, the pooled results for 7 observational studies showed that breastfeeding at the time of gluten introduction has no effect on the risk of developing CD compared with formula feeding (OR 0.88, 95% CI 0.52-1.51) [10] .…”
Section: Breastfeeding At the Time Of Gluten Introductionmentioning
confidence: 65%
“…A prospective Generation R cohort including 1,679 Dutch children positive for HLA-DQ2 and/or DQ8 evaluated the possible association of the timing of gluten introduction and breastfeeding duration with CD autoimmunity at 6 years of age. It was shown that breastfeeding for longer than 6 months was not related to a lower risk of CD autoimmunity [31] . Interestingly, the Norwegian Mother and Child Cohort Study (MoBa) involving more than 100,000 children showed that breastfeeding for longer than 12 months was associated with a higher risk of CD [32] .…”
Section: Exclusive or Any Breastfeeding And Duration Of Breastfeedingmentioning
confidence: 99%
See 3 more Smart Citations